Pregnancy? Attention to these points - ES Hajikazemi (Iran University of Medical Sciences, 1995)
If all pregnant women worry about their fetus, worries of pregnant nurses are more serious and actual. Which groups of women have more chance about hydatidform mole, amniotic fluid embolism or Sheehan's syndrome? Fortunately, these complicated problems are very rare but what about daily injuries due to infectious diseases, radioactive substances, anticancer drugs and other chemical substances? Also, when you change position of patients, you may be injured. These instances can jeopardize your health and fetus. There are some worthy points that if you consider them, protect yourself and your fetus from any damage